Functional stability and structural transitions of a kunitz trypsin inhibitor from chickpea (CaTI2) - Bendre, Ameya D.; Shukla, Ekta; Ramasamy, Sureshkumar (Protein Journal, 2020)
Enzymes are important tools for various applications. We have studied structural transitions and functional stability of a Kunitz trypsin inhibitor from Chickpea (CaTI2), a potent insect gut-protease inhibitor, under different stress conditions like non-neutral pH, elevated temperature and co-solvent concentrations. CaTI2 was cloned and expressed in an eukaryotic systemP. pastorisand was investigated for conformational transitions using circular dichroism spectroscopy, differential scanning fluorimetry and activity assay. Native CaTI2 has a sheet dominant structure with 40% beta sheets and possess a single tryptophan residue situated in the hydrophobic core of the enzyme. The recombinant inhibitor maintained its maximum activity under alkaline pH with its secondary structure intact between pH 6-10. CaTI2 was observed to be thermally stable up to 55 degrees C with aT(m) of 61.3 degrees C above which the protein unfolds. On treating with chemical denaturant (urea), the CaTI2 lost its inhibitory potential and native conformation beyond 2 M urea concentration. Moreover, the protein unfolded at lower temperatures as the concentration of denaturant increased, suggesting more complex structural changes. Further, the stability of the inhibitor was found to be directly proportional to the solvent polarity. The data, herein offers significant information of inhibitor stability and activity which could be exploited for its further development into an effective pesticide. [GRAPHICS] .
Keywords: Chickpea; Circular dichroism spectroscopy; Differential scanning fluorimetry; Functional stability; Kunitz trypsin inhibitor